Effects of copper exposure and increased temperatures on Collembola in western Washington, USA. (December 2019) - Callahan, Sean T.; Bidwell, Amanda; Lin, Constance; DeLuca, Thomas H.; Tobin, Patrick C.
Abstract: In the city of Seattle and the surrounding Puget Sound region, increased human population and the resulting increased domestic and commercial transportation has led to higher inputs of heavy metal pollutants in the region, many of which have been shown to increase in toxicity for various organisms at higher temperatures. One pollutant of concern in the region is copper (Cu) from brake and tire attrition. The extent to which Cu can affect other organisms that are part of the Puget Sound ecosystem is largely unknown. We studied the effect of Cu exposure on two species of Collembola, one of which is a native species ( Choreutinula americana Palacios-Vargas, Castaño-Meneses & Gao) inhabiting the region's epiphytic mosses and lichen while the other is a model species commonly used in ecotoxicology studies ( Folsomia candida Willem). We then extended this work by examining the effect of Cu exposure when Collembola are exposed to increased temperatures as predicted by the B1 and A2 climate change scenarios. We found that the native Collembolan was significantly more sensitive to Cu than the model species when maintained under a constant 20 °C, suggesting that ecotoxicology studies using the model species F. candida might underestimate the effect of toxicants to native Collembola. We also observed that increased temperatures significantly lowered the tolerance of both species to Cu. The results of this study highlight the joint effect of warming temperatures and pollutants on a representative species of Collembola in the Pacific Northwest. Highlights: Copper pollution in cities can occur through brake and tire attrition. Copper exposure negatively affects microarthropods. Findings from model species underestimated Cu affects to naturally-occurring species. Warming temperatures exacerbate the negative effect of Cu to microarthropods.